Arab economies in the twenty-first century - Rivlin, Paul (Cambridge University Press, 2009)
"This book examines the relationship between demographic growth and economic development in eight Arab countries. Despite a slowdown in demographic growth, the labor force is increasing rapidly because of the change in the age structure of the population. In other parts of the world, similar developments have enhanced economic growth. In the Arab world, however, many of the opportunities presented by demographic transition are being lost, resulting in serious threats to the political stability of the region. The main reason for this is that the region has missed out on industrialization."--Jacket